OM SANDALFØDDER OG MULIGHEDEN FOR FORANDRING - Dalsgård, Anne Line (Tidsskriftet Antropologi, 2002)
both the inferiority experienced by lowerclass Brazilians and the particular role of storytelling in the communication of anthropological insights. The two aspects of the article are related through the use of stories (here defined as recounts of particularly revealing moments during field-work) in the description of a metaphorical relationship between broad feet, poverty and second-class citizenship. Brazil is a society penetrated by social inequality in all aspects of daily life. The media bombardment of advertisements for products of all sorts increases the sense of inferiority among the poor. Signs on the body like grey, uncared-for skin and broad feet due to sandal use are experienced as the embodiment of ignorance and lack of selfcontrol. The informant Sonia explains the position as a “sandal foot” (pé de chinelo) with her story about lack of recognition and an often violent attitude towards lower-class Brazilians in the sphere of consumption as well as the health care system. In addition, a particular situation is described, in which the anthropologist witnesses a medical doctor misread a poor woman’s attempt to appear respectable. The anthropologist feels her impotence and detachment as an observer, while she dressed as a nurse unwillingly participates in the humiliation of the woman. This kind of experience, it is argued, provides a broadened understanding of human ex-perience, which may renew – in the anthro-pologist as well as her reader – the respect for the Other, crucial to any struggle for rights on a formal, and in the common sense, political level. The use of stories as vehicles for this kind of understanding and, more pragmatic-ally, for the anthropologist’s viewpoint in a highly politicized debate is justified by the particular capacity of storytelling. Stories about moments during fieldwork merge the “knower” and the known, it is argued, and engage the reader’s imagination and experience in the attempt to follow the process of knowing. They may therefore provide a richer understanding of anthro-pological insights than descriptions based on information and explanation alone. Besides, stories are per definition positioned, as there would be nothing to tell if nobody had sensed, felt and thought anything. Therefore, the telling of stories clearly engages the reader in an interpretation of the relationship between field, anthropologist and text. These two aspects of storytelling, the transportation of the reader to the field site by way of imagination, and the demand on the reader’s ability to interpret told situations, allow for a reflection upon human conditioning and the resulting plurality of perspectives. It also allows the anthropologist to put forward her perspective without postulating any superior knowledge.